2013
DOI: 10.1371/annotation/8b818c15-3fe0-4e56-9be2-e44fd1ed3fae
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Trichoderma-Plant Root Colonization: Escaping Early Plant Defense Responses and Activation of the Antioxidant Machinery for Saline Stress Tolerance

Abstract: Trichoderma spp. are versatile opportunistic plant symbionts which can colonize the apoplast of plant roots. Microarrays analysis of Arabidopsis thaliana roots inoculated with Trichoderma asperelloides T203, coupled with qPCR analysis of 137 stress responsive genes and transcription factors, revealed wide gene transcript reprogramming, proceeded by a transient repression of the plant immune responses supposedly to allow root colonization. Enhancement in the expression of WRKY18 and WRKY40, which stimulate JA-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 55 publications
2
43
0
Order By: Relevance
“…However, a significant variability in their PGPF traits was observed. T1 exhibited a significantly stronger P solubilization ( Supplementary Table S1) and much higher IAA induction (Supplementary Table S1), as compared with T2, suggesting that T1 might likely act through auxin-dependent mechanism as plant growth stimulator as reported for several PGPFs isolated earlier [9,32,33]. In agreement with this finding, T1-treatment enhanced germination of onion seeds, seedling weight and height when compared with T2-treatment and SDW-treated control (Fig.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, a significant variability in their PGPF traits was observed. T1 exhibited a significantly stronger P solubilization ( Supplementary Table S1) and much higher IAA induction (Supplementary Table S1), as compared with T2, suggesting that T1 might likely act through auxin-dependent mechanism as plant growth stimulator as reported for several PGPFs isolated earlier [9,32,33]. In agreement with this finding, T1-treatment enhanced germination of onion seeds, seedling weight and height when compared with T2-treatment and SDW-treated control (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…3 and Supplementary Table S2) revealed a substantial accumulation in these metabolites in the T1-and T1+FOC-primed onion plants compared with control, which provides a building stone to the functional role of the Trichoderma-primed onion against ROS accumulation generated by abiotic or biotic stress. Our finding was in harmony with the work of Brotman et al, [32], which reported the activation of antioxidant systems in Trichoderma-Arabidopsis.…”
Section: Thus Our Data Have Made a Clear Discrimination Between The supporting
confidence: 93%
See 1 more Smart Citation
“…Other studies have shown that different T . harzianum strains can induce systemic resistance against necrotrophic pathogens in different crops [15, 5355]. …”
Section: Discussionmentioning
confidence: 99%
“…is soil-borne, versatile opportunistic plant symbiont that induces growth and resistance to a wide variety of phytopathogens [13, 15]. It has been reported that some Trichoderma spp., can stimulate ISR in crops via signaling molecules, such as jasmonic acid (JA), ethylene (ET), and salicylic acid (SA), to plant diseases caused by biotrophic or necrotrophic pathogens, such as S .…”
Section: Introductionmentioning
confidence: 99%